Application of Piecewise Successive Linearization Method for the Solutions of the Chen Chaotic System. (15th July 2012) - Motsa, S. S.; Khan, Y.; Shateyi, S.
Abstract : This paper centres on the application of the new piecewise successive linearization method (PSLM) in solving the chaotic and nonchaotic Chen system. Numerical simulations are presented graphically and comparison is made between the PSLM and Runge-Kutta-based methods. The work shows that the proposed method provides good accuracy and can be easily extended to other dynamical systems including those that are chaotic in nature.